Only what does not fit in can be true: de-professionalisation and academia in relation to Adorno and Tagore - Chaudhuri, Rosinka (2016)
This paper explores de-professionalisation--interpreted here as the experience of finding that the work one does, does not fit into the demands of the profession-- in the context of Theodor Adorno and Rabindranath Tagore. While both were writers, they were also part of the academic world and it is their grappling with the demands of academia that this paper looks into and elucidates. - Reproduced.
Keywords: Tagore, Rabindranath; Adorno, Theodor; Eminent personalities